The Effect of Parents' Schooling on Child's Schooling: A Nonparametric Bounds Analysis - Monique de Haan (Tinbergen Institute, 2008)
This paper uses a relatively new approach to investigate the effect of parents' schooling on child's schooling; a nonparametric bounds analysis based on Manski and Pepper (2000), using the most recent version of the Wisconsin Longitudinal Study. We start with making no assumptions and then add some relatively weak and testable assumptions to tighten the bounds. Although the bounds on the treatment effects include a zero effect, the upper bounds are informative especially for the effect of increasing parents' schooling from a high school degree to a bachelor's degree. Both for the effect of mother's schooling as for the effect of father's schooling the nonparametric upper bounds are significantly lower than the OLS results.
Keywords: I2; J62; C14; 330; Intergenerational mobility; nonparametric bounds analysis; education; Bildungsniveau; Eltern; Bildungsverhalten; Kinder; Nichtparametrisches Verfahren; Wisconsin; USA